Artificial intelligence : a modern approach - Russell, Stuart J. (Stuart Jonathan); Norvig, Peter (Upper Saddle River , N.J. : Prentice Hall, 1995)
A highly accessible, up-to-date professional reference for programmers, software engineers, system administrators, or technical managers, this book integrates state-of-the-art AI techniques into intelligent agent designs using examples and exercises to lead the reader from simple reactive agents to full knowledge-based agents with natural language capabilities.
Includes bibliographical references (p. 859-903) and index.
Keywords: Artificial intelligence; Computing